Inkonsistensi Putusan Peradilan Dan Kepastian Hukum Dalam Pemilihan Kepala Daerah Di Indonesia - BRYAN LUCKY LUCIANO; GIOVANNI YONATHAN; HESTI ARMIWULAN; ERLY ARISTO (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The 1945 Constitution of the Republic of Indonesia establishes a state based on the rule of law, mandating strict legal certainty under Article 28D. However, the administration of the Regional Head Elections revealed a critical systemic vulnerability characterized by conflicting judicial interpretations regarding candidate eligibility between the Supreme Court and the Constitutional Court. This study aims to analyze the systemic legal uncertainty generated by Supreme Court Decision No. 23/P/HUM/2024, which retroactively altered the gubernatorial age benchmark to the time of inauguration and to comprehensively examine the remedial role of Constitutional Court Decision No. 70/PUU-XXII/2024. Employing a normative juridical research design, this study utilizes a statutory approach to analyze the hierarchy of electoral norms alongside a conceptual approach to dissect the jurisprudential coherence of both decisions against the doctrine of Lex Certa and Open Legal Policy. The research demonstrates that the Supreme Court's expansive interpretation created a severe